DEMOCRATIC LEADERSHIP IN IMPROVING LIBRARY STAFF PERFORMANCE - Agustina, Gina; Kuswati, Suci Nurrahma (PERSPEKTIF: Journal of Social and Library Science, 2023)
This article is entitled Democratic Leadership in Improving the Performance of Library Staff at the Tembilahan Riau Regional Library and Archives Service, which aims to find out what forms of democratic leadership are applied by library heads to improve staff performance in regional libraries. This article uses descriptive qualitative methods with surveys and interviews as data collection techniques. The results show that the leader includes staff in planning related to librarianship, the leader directs and motivates staff to improve performance, the leader supports professional development and training of librarians to improve staff professionalism, the leader has an open attitude towards staff and is communicative to subordinates and provides supervision. to staff.